Fenomena Literasi Spasial pada Siswa Kelas VII SMP Materi Bangun Datar - Nuraeni Mauliddatul Fikria; Indah Rahayu Panglipur; Marsidi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2023)
Spatial literacy is an important component that students must master. Spatial literacy supports students' understanding of flat shapes which are closely related to the real world. This study aims to describe the phenomenon of spatial literacy in student studies on flat shapes. This research design uses a descriptive with a qualitative approach. Data collection techniques used in this study were observation, pretest & posttest, and interviews. The research location in this study was VII Minqhotrotul Ulum Gumukmas Middle School. The subjects in this study consisted of 3 students who had high mathematical abilities and 2 students who had low mathematical abilities. The results of this study indicate that students who have high abilities can sketch spatial objects through visual images based on contextual problems, identify questions and statements of mathematical models and relate concepts and spatial object relationships in calculation techniques and are able to express ideas related to spatial object relationships through oral and written . Whereas students who have low mathematical abilities have known that a phenomenon cannot create spatial objects through visual images based on contextual problems, is unable to express ideas related to spatial object relationships through speech and writing, but can identify questions and statements of mathematical models, but cannot relate concepts and spatial object relationships in calculation techniques. so from this phenomenon it can be concluded that students who have high mathematical abilities have fulfilled the three aspects of spatial literacy indicators, namely the aspects of Visualization, Reasoning, and Communication, and students who have low mathematical abilities do not fulfill the three aspects of spatial literacy indicators. Keywords: Phenomena, Spatial Literacy, Flat Shape Study.